Knowledge, awareness and dietary practice on urolithiasis among general population in Kuantan, Pahang, Malaysia: Preliminary findings - Siti Noorkhairina Sowtali; Siti Roshaidai Mohd Ariffin; Nor Syawanidamia Nazli; Nor Azwani Binti Mohd Shukri; Muhammad Muzaffar Ali Khan Khattak; Islah Munjih Ab Rashid; Suhana Binti Muhamad; Fatin Noraliah Adzali (SAGE Publishing, 2021)
Background: To date, no studies have been published at evaluating the level of knowledge, awareness and practice of dietary, particularly regarding to urolithiasis in patients or the general population. This study aims to provide basic information on the level of knowledge, awareness and dietary practice among general population in Kuantan, Pahang. Design and Methods: The respondents (n=30) were conveniently recruited within 10 kilometres radius of Kuantan city. The data were obtained using semi-guided administered questionnaires, which consists of four parts: socio-demographic data, lifestyle and clinical history (Part A); attitude and awareness on dietary practice regarding urolithiasis (Part B); food frequency questionnaire on urolithiasis (Part C) and level of knowledge on urolithiasis (Part D). Results: Majority of the respondents were women (70%), Malay (83.3%), mean age of 33.97 (±9.27), married (63.3%), completed higher education level (60%), working with government sector (33.3%) and have fixed monthly income (53.3%). Some of them had hypertension (n=4), diabetes (n=1), gout (n=1) and intestinal problem (n=1). Majority (80%) claimed having no family history of urolithiasis, consumed alcohol (10%), exercise with average frequency 2-3 times/week (46.7%) and heard about urolithiasis from healthcare worker (46.7%). The respondents' awareness about urolithiasis is considered to be good [81.23 (±9.98)] but having poor knowledge score [2.70 (±1.149)]. Majority preferred wholemeal bread, white rice, chicken meat, mackerel fish, chicken egg, apple, carrot, mustard leave and fresh milk in daily intake. Lesser plain water intake than standard requirement was noticed among respondents. Seasoning powder was commonly used for seasoning. Conclusions: Generally, the general population of Kuantan, Pahang was aware of urolithiasis disease but needed more information on dietary aspect in terms of knowledge and food choice.